Oil separation process of Citrus sinensis orange: simulation and techno‐economic evaluation. (13th April 2022) - Santos, Victor de M; Calado, Veronica M. A.; Bojorge, Ninoska
Abstract: This work focuses on modeling, simulation and techno‐economic analysis, motivated by the great potential for transforming the residues of sweet orange peel ( Citrus sinensis ) from the food industry into products with higher added value. A techno‐economic analysis of the extraction process of limonene and linalool using supercritical CO2 in a continuous flow was carried out on an industrial scale. The process was simulated using the Soave–Redlich–Kwong (SRK) thermodynamic equilibrium model. In order to find the maximum separation process yield, a 3 3 factorial design was used to analyze the main process factors, which were temperature, pressure, and solvent feed rate. Limonene was the principal component extracted. The optimum conditions for limonene extraction using a 12‐stage differential extractor were 50°C, 1930 kg h −1 and pressure around 74 bar, representing a 99.5% extraction from orange peel oil. The analyzed process conditions showed that the solution became saturated when the CO2 /oil feed ratio was >19.7 kg h −1 . Under these conditions, the cost of manufacturing was US148.04 per kg of orange peel oil. © 2022 Society of Chemical Industry and John Wiley & Sons, Ltd